Internalization of Character Values Through Islamic Religious Education Learning Among Students at Junior High School of Al-Azhar Mandiri Palu - Nur Fhatila Dini; Adawiyah Pettalongi; Ubadah Ubadah (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2026)
This study examines the internalization of character values through Islamic Religious Education (PAI) learning among students at SMP Al-Azhar Mandiri Palu. Using a qualitative approach with a case study design, data were collected through observations, interviews, and documentation involving school principals, teachers, students, and parents. The findings reveal that character values are internalized through classroom learning, religious habituation, exemplary behavior, extracurricular activities, and collaborative interactions between teachers and students. Islamic Religious Education teachers play a central role in integrating character values such as discipline, responsibility, honesty, respect, and religiosity into both learning activities and students’ daily behavior. The study also found that support from the school environment and parents strengthens the effectiveness of character education implementation. Therefore, the internalization of character values through PAI learning contributes significantly to shaping students’ moral character and positive behavior in the school environment.